LASER-TISSUE INTERACTION: A BIOPHYSICAL STUDY FOR PRECISION SURGICAL APPLICATIONS - Sabah Mhana, Malak; Ahmed Hadad, Mariam; salam obaed, Rusul; Abd Al-Abbas Hassan Haddahood, Walaa; Najm, Samara Salih (Journal of Medical Genetics and Clinical Biology, 2025)
Objective: This study aims to deepen the understanding of laser-tissue interactions in precision surgery by evaluating the biophysical mechanisms influenced by specific laser parameters and tissue characteristics. Method: A literature-based analytical approach was employed to explore the effects of key laser-tissue interaction types—photothermal, photochemical, photomechanical, and photoablation—focusing on variables such as wavelength, pulse duration, and fluence. Results: The analysis revealed that different laser systems, including CO₂, Nd:YAG, and femtosecond lasers, exhibit distinct interaction profiles across clinical applications, significantly affecting surgical outcomes. Furthermore, the integration of artificial intelligence, nanotechnology, and real-time feedback systems was found to enhance the precision, safety, and personalization of laser-based procedures. Novelty: This study provides a comprehensive synthesis of wavelength-specific and tissue-dependent laser effects, while highlighting the emerging potential of interdisciplinary innovations to transform laser-assisted surgeries. It underscores the critical role of smart technologies in advancing minimally invasive techniques and calls for further cross-domain research to optimize future clinical applications.